Aplicación de la Contabilidad Comercial a la Distribuidora Chamba Vega del Cantón Centinela del Cóndor, Periodo Julio-Septiembre/2014 - Vaca Gaona, Andreina Liliana (2015)
The thesis entitled “APLICACIÓN DE LA CONTABILIDAD COMERCIAL A LA DISTRIBUIDORA CHAMBA VEGA DEL CANTÓN CENTINELA DEL CÓNDOR, PERIODO JULIO-SEPTIEMBRE/2014”, is justified significantly, and that aims to organize accounting so that distributor entitles the owner to obtain accounting and timely financial information for decision-making. With the implementation of commercial accounting were met the objectives set , which came to strengthen the financial management of the distribution , becoming an important contribution to the growth and development of their business , starting with the design of the Plan and Manual accounts according to business needs thereof; we continued obtaining Initial Inventory having a value of $ 77.814.66 , preparation of memorandum Journalize operations to proceed in the Daybook ; then he continued with the majorization of each of the accounts from the exercise to continue the Trial Balance, Worksheet , finally the presentation of financial statements , by which it was possible to clearly present all accounts and balances , revealing the economic benefits or not obtained within the specified period for the study. Upon completion of this work it will be unveiled to the owner, that during the period July / September obtained a loss in economic activity in the amount of $ 66,157.83; because it must take into account the respective conclusions as the preparation and presentation of financial statements as allow you to get timely information that are alternative solutions, change and better performance for your distributor